Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.2337/dc07-0196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LDL Cholesterol and Treatment With Losartan on End-Stage Renal Disease in the RENAAL Study

Abstract: Renal pathology and dyslipidemia commonly coexist. Treatments that lower albuminuria/ proteinuria may lower lipids, but it is not known whether lipid lowering independent of lessening albuminuria/proteinuria slows progression of kidney disease. We examined the association between LDL cholesterol levels and treatment with losartan on end-stage renal disease (ESRD). Lipid levels and albuminuria measurements were obtained at baseline and at year 1 in a post hoc analysis from the Reduction of Endpoints in NIDDM wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This might be due to the lipid-lowering effects of the valsartan plus amlodipine therapy observed in the present study. Since lowering serum LDL levels was positively associated with the reduction in albuminuria [19] , addon amlodipine therapy could decrease UAE to a level similar to add-on hydrochlorothiazide therapy in the patients treated with valsartan. This was also supported by the ANCOVA analysis showing that the decrease in plasma TC level with valsartan plus amlodipine therapy significantly contributed to the decrease in UAE.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the lipid-lowering effects of the valsartan plus amlodipine therapy observed in the present study. Since lowering serum LDL levels was positively associated with the reduction in albuminuria [19] , addon amlodipine therapy could decrease UAE to a level similar to add-on hydrochlorothiazide therapy in the patients treated with valsartan. This was also supported by the ANCOVA analysis showing that the decrease in plasma TC level with valsartan plus amlodipine therapy significantly contributed to the decrease in UAE.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding 24hrs urinary proteins, statistically significant differences were found among studied patients, with 76.7% reduction in losartan group and 45.6 % reduction in enalapril group than which was only 4% reduction in non treated group .This result came in agreement withWebb et al [14] study which reported sustained reduction of proteinuria in losartan group and in enalapril group after 3 years of follow-up, and losartan was comparable in terms of efficacy and safety to enalapril.Also with Wuhl et al [16] studywhich reported that there is significant reduction from baseline proteinuria in both enalapril group and losartan group after 6 months of treatment. Also with Ellis et al [17] study which demonstrated that protein excretion decreased after a mean period of 1.9 months with maximal and sustained decrease in proteinuria occurred after a mean of 4.7 months after starting losartan and with Web et al [7] study which reported that losartan significantly reduce proteinuria as compared to amlodipine or placebo.…”
Section: Therementioning
confidence: 78%
“…This post hoc analysis focuses on the response to multiple markers including systolic blood pressure (SBP), albuminuria, serum potassium, haemoglobin, total cholesterol and uric acid. These markers were selected since prior studies have shown that intervention in the RAAS can affect these risk marker levels when compared with placebo . Uric acid was not included in the analysis for the IDNT and IRMA‐2 trials, as it was previously shown that irbesartan does not affect this risk marker .…”
Section: Methodsmentioning
confidence: 99%
“…However, blood pressure is not the only risk marker that is influenced by intervention in the RAAS. Intervention in the RAAS has a broad spectrum of effects on other renal risk markers including decreasing albuminuria, haemoglobin, uric acid, cholesterol and increasing potassium . Changes in these renal risk markers have implications for patients’ clinical prognosis.…”
Section: Introductionmentioning
confidence: 99%